PENGARUH SUPERVISI AKADEMIK DAN PARTISIPASI GURU DALAM KKG TERHADAP KOMPETENSI PROFESIONAL GURU SD KECAMATAN SAJAD - Aswindirno, Aswindirno; Sukmawati, Sukmawati; Suib, Masluyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:This research generally aims to reveal the influence of academic supervision and teacher participation in the KKG to the professional competence of teachers of State Elementary School in Kecamatan Sajad. This research uses quantitative approach. The data used is quantitative data. The population in this study amounted to 104 teachers. While the sample amounted to 77 teachers. Data were collected using questionnaires by measurement model using Likert scale. The collected data is tabulated. Then performed the analysis using the help of computer application program, namely SPSS version 24 for Window. Data analysis uses descriptive statistics and inferential statistics. The results showed that 1) the influence of academic supervision (X1) on teacher professional competence (Y) Beta (b1) of 0.415 = 41.50%; 2) teacher participation in KKG (X2) on teacher professional competence (Y) Beta ) By 0,303 = 30.30%; 3) the influence of academic supervision (X1) and teacher participation in KKG (X2) on professional competence of teacher equal to 0,373 or 37,30%. The result of F test seen on the ANOVA output from multiple linear regression analysis shows that Fcount> Ftable(21,985>3,105).The conclusions of this study are as follows: 1) the supervision of elementary school students in Sajad sub-district is quite good, 2) teacher participation in KKG SD Negeri in Sajad sub-district is high, 3) the professional competence of teachers of SD Negeri in Sajad sub district is high, 4) (5) teachers' participation in KKG significantly influence the professional competence of teachers of SD Negeri in Kecamatan Sajad, and 6) Academic supervision and teacher participation in KKG together significantly influence on competence Professional teacher of SD Negeri in Kecamatan Sajad. Keyword: Academic Supervision, Teacher Participation in KKG, Professional Teacher Competency.